Genetic variability, character association and path analysis for yield and yield attributing traits in lettuce (Lactuca sativa) - SINGH, S R; RAJAN, S; VEENA, G L; KUMAR, DINESH; MURALIDHARA, B M; SRIVASTAVA, K K (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted to assess the genetic variability and relationship among the important horticultural traits in lettuce (Lactuca sativa L.). A wide range of variability among selected genotypes was observed for specific traits. A little or very less difference was observed between the genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) for all traits indicated the least environmental influence, which suggests that selection can be done based on the phenotypic performance. Higher estimates of heritability coupled with higher genetic advance for plant weight, yield, average leaf weight, leaf width indicated the presence of additive gene action, through which selection can be done. Yield (q/ha) showed highly significant positive correlation with plant weight, stem diameter, leaf size at genotypic and phenotypic level. Significant positive direct effect on yield by average plant weight, leaf length, average leaf weight and stem diameter and their significant positive correlation with yield as well as high heritability coupled with high genetic advance suggested them as the most important components contributing to yield. Thus, more weight should be given to these traits in yield improvement programme of lettuce for future line of work.